Evaluation of the effect of diode laser for debonding ceramic brackets on nanomechanical properties of enamel - Sinaee, Neda (Dent Res J (Isfahan), 2018)
BACKGROUND: The heat from laser can lead to the destruction of organic components of enamel and consequently changes in the mechanical properties of enamel. The purpose of this study was to evaluate the effect of diode laser on the nanomechanical properties of enamel in the process of debonding the ceramic brackets. MATERIALS AND METHODS: In This in vitro study Eighteen ceramic brackets were bonded on the intact premolars in 3 groups of 6 (one control and two study groups). To debond the brackets in the study groups, laser diode was used for 3 s with 1W and 3W power. Shear bond strength and adhesive remnant index were recorded for all groups. Hardness and elastic modulus were measured in 1–31 μ depth from enamel surface in each debonded area. Analysis of variance was used for determining the difference in shear bond strength (SBS), hardness, and elastic modulus and was followed by post hoc Tukey's honest significant difference test. One-sample t-test was used to compare the changes in the pulp temperature with the standard threshold (5.5°C). The significance level was set at %5 in this study. RESULTS: SBS was significantly greater in the control group compared to the study groups. There was no significant difference in the average of hardness and elastic modulus of enamel between the groups. Pulp temperature elevation in the study groups was significantly < 5.5°C (P = 0.000). CONCLUSION: The diode laser with either 1W or 3W power for 3 s is effective in debonding the ceramic brackets without any detrimental effect on the pulp or mechanical properties of enamel. In regard to the pulp health, the 1W power laser is rather recommended for debonding the ceramic brackets than the 3W laser power.